Linear Algebra a Course for Physicists and Engineers - Mathai, Arak M. (De Gruyter Textbook, 2017)
In order not to intimidate students by a too abstract approach, this textbook on linear algebra is written to be easy to digest by non-mathematicians. It introduces the concepts of vector spaces and mappings between them without dwelling on statements suc.